Increased Caribbean seismicity and volcanism during minima in Earth’s rotation rate: Search for a physical mechanism and a 2030 forecast - Bilham, Roger; Szeliga, Walter; Mencin, David; Bendick, Rebecca (Frontiers in Earth Science, 2022)
Three quarters of all Mw≥6.6 earthquakes and volcanic eruptions surrounding the Caribbean plate occur preferentially during periods of decadal minimum slowing in Earth’s angular spin velocity. This correlation is revealed most clearly as a 4-6 year phase lag following the first derivative of the length of the day (LOD), Earth’s angular deceleration. We show that local strains and displacements resulting from oblateness changes, or plate boundary stresses associated with changes in tropical rotation rates are orders of magnitude lower than those typically associated with earthquake or volcano triggering. Notwithstanding the absence of a satisfactory causal physical mechanism, the relationship permits decadal trends in Caribbean tectonic hazards to be anticipated many years before their occurrence. The next period of increased tectonic activity in the Caribbean, corresponding to a probable slowing in Earth’s spin rate, will occur in the decade starting on or about 2030.